Increased macrophages contribute to thyroid hormone-induced cardiac alterations in mice - Senger, Nathalia; de Almeida-Santos, Gislane; Cerri, Gabriela Cavazza; Mota, Joice Silva; Parletta, Aline Cristina; Vieira-Junior, Denival Nascimento; Junior, Joaquim Teixeira Xavier; do Nascimento, Rogério Silva; da Silva Ramos de Souza, Danilo Chaves; Irigoyen, Maria Claudia Costa; Diniz, Gabriela Placoná; Mosig, José Maria Alvarez; et al. (Acta physiologica, 2025)
Aims The heart is one of the main targets of thyroid hormone. Patients with hyperthyroidism, a disease with high incidence in the population, have increased arrhythmia risk and cardiac hypertrophy, which is an independent predictor of adverse cardiovascular outcomes. Recent research has revealed the essential roles of leukocytes in cardiac homeostasis and stress-induced responses. Here, we aimed to evaluate the role of immune cells in cardiac changes induced by elevated triiodothyronine (T3) levels. Methods The hyperthyroid condition in mice was mimicked by daily injections (i.p.) of T3 (14 μg/100 g BW) for 7 or 14 days. Results Increased heart rate and cardiac mass observed after 7 days of T3 treatment was associated with enhanced myocardial population of neutrophils, dendritic cells, and inflammatory phenotypes of monocytes and macrophages, without circulating changes in these cells, as evaluated by flow cytometry. In vitro experiments demonstrated bias toward pro-inflammatory polarization in isolated bone marrow-derived macrophages (BMDM) in response to T3. Interestingly, depletion of macrophages in mice prevented hypertrophic heart growth, tachycardia, and increased gene expression of the pro-inflammatory cytokine interleukin-(IL)-6 caused by hyperthyroid condition. Conclusion Together, these new findings indicate the involvement of macrophages in the cardiac changes promoted by higher T3 levels. Considering that sustained cardiac growth and tachycardia can potentially lead to heart failure, our results suggest that targeting macrophages might be a novel therapeutic approach for attenuating cardiac disorders caused by hyperthyroidism.
Online veröffentlicht: 7. Februar 2025
Gesehen am 31.07.2025